Development and supply strategy of cocoa commodity effect to cocoa farmers revenue in Boalemo District - Abdurrahman Pakaya; Amir Halid; Hermanto Payuyu (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
This study purpose to analyze the influence of development strategy and supply chain of cocoa commodity to cocoa farmer income. This research conducted in Boalemo District with research method using stratified random sampling technique with data analysis used is multiple linear regression analysis. The result of this research stated that partially cocoa commodity development strategy in Boalemo District give positive influence to farmer's income but has not give significant influence to farmer's income. Partially supply chain gives positive effect to cocoa farmer income in Boalemo District, beside giving positive influence, supply chain also give significant influence to cocoa farmer income in Boalemo District, and for dummy of influential sub-district that is Tilamuta sub-district, followed by Sub-district Dulupi and after that Botumoito District. Simultaneously, development strategies and supply chains have a positive and significant impact on cocoa farmers income in Boalemo District.